2021
DOI: 10.1136/bmjopen-2021-049405
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination as a predictor of poor mental health among LGBTQ+ people during the COVID-19 pandemic: cross-sectional analysis of the online Queerantine study

Abstract: ObjectivesTo assess the mental health and experiences of discrimination among lesbian, gay, bisexual, transgender, queer (LGBTQ) people at the start of the COVID-19 pandemic.DesignData come from a cross-sectional online survey targeted at LGBTQ+ people, which collected data on mental health, experiences of discrimination and a number of other pandemic-related experiences. To examine the association between sexual orientation and gender and mental health and experiences of discrimination, we conducted regressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 42 publications
2
35
0
7
Order By: Relevance
“…Although mental health inequities existed for SGM before the pandemic, various social and mental health inequities have been exacerbated during the COVID-19 pandemic due to the provincial mandates to physical distancing orders and service closures. Our research aligns with the existing body of literature, which has identified that the mandates for physical distancing and self-isolation have contributed to particular forms of exclusion, social isolation and reduced social support for SGM (Daly et al, 2021; Kneale & Bécares, 2021). The COVID-19 pandemic is particularly concerning for SGM who may have recent and acute experiences of minority stress, and may also be experiencing isolation and separation from affirming persons, resources, social outlets, and supports (Brennan et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Although mental health inequities existed for SGM before the pandemic, various social and mental health inequities have been exacerbated during the COVID-19 pandemic due to the provincial mandates to physical distancing orders and service closures. Our research aligns with the existing body of literature, which has identified that the mandates for physical distancing and self-isolation have contributed to particular forms of exclusion, social isolation and reduced social support for SGM (Daly et al, 2021; Kneale & Bécares, 2021). The COVID-19 pandemic is particularly concerning for SGM who may have recent and acute experiences of minority stress, and may also be experiencing isolation and separation from affirming persons, resources, social outlets, and supports (Brennan et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…measured before and during the crisis, sexual minority men showed higher levels during the crisis compared to heterosexual men, which remained significant after baseline adjustment for depression and sleep quality, meaning that the gap in these measures between sexual minority men and heterosexual men increased during the crisis, even if there was no absolute increase (and even a decrease for depression) in these measures early in the crisis (42). Earlier research had reported the high impact of the COVID-19 crisis on sexual minority men (23)(24)(25)(26)28), but also on the general population (32), it was therefore important to test whether sexual minority men were indeed more affected than heterosexual men. Only relatively few studies mostly based on online convenience samples from the United States of America (9, 33-39), had reported a higher psychological impact of the COVID-19 crisis among sexual minorities compared to heterosexual people.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, these factors may predispose sexual minorities to a worse reaction to the crisis (6,8) and their existing higher addictive behaviors and substance use (14) may also be further exacerbated as a coping mechanism for COVID-19's psychological impact. Recent research has indicated that members of sexual minority groups have suffered a high psychological impact from the crisis (23)(24)(25)(26)(27)(28)(29)(30)(31), but these studies were done in samples of sexual minority people only and, therefore, that impact cannot be compared with the psychological impact suffered by the heterosexual people also affected by the crisis (32). Seven studies with online recruited convenience samples from the United States of America (9,(33)(34)(35)(36)(37)(38) and one online study conducted in Portugal and Brazil (39) comparing sexual minorities and heterosexual persons found that the psychological impacts among members of sexual minorities were greater.…”
Section: Introductionmentioning
confidence: 99%
“…This could have the consequence of trans populations either being asked inappropriately to shield, or not to have been invited to shield even when this would have been the most appropriate course of action. Evidence on the experience of LGBTQ+ communities during the pandemic to date has mainly been based on data from online convenience samples [14].…”
Section: Introductionmentioning
confidence: 99%